Mechanism and molecular weight model for thermal oxidation of linear ethylene-butene copolymer - Chiantore, O. (2001)
The mechanism of thermooxidative degradation at 80°C of a narrow distribution linear ethylene-butene copolymer has been described by determining the chemical modifications and molecular weight distribution changes occurring in the polymer chains, and successively fitting the experimental results with a mathematical model which allows scission and crosslinking reactions to occur simultaneously. Degradation takes place with autoacceleration and from the computer simulation a cubic dependence of the degree of crosslinking and degree of scission with exposure time was obtained. It was established that in this system scissions predominate over crosslinking, in accordance with the drop in average molecular weights and the concomitant accumulation of oxidation products.